Quality of life in patients with TIA and minor ischemic stroke. (1st December 2015) - Sangha, Rajbeer S.; Caprio, Fan Z.; Askew, Robert; Corado, Carlos; Bernstein, Richard; Curran, Yvonne; Ruff, Ilana; Cella, David; Naidech, Andrew M.; Prabhakaran, Shyam
Abstract : Objective: We investigated health-related quality of life (HRQOL) in patients with TIA and minor ischemic stroke (MIS) using Neuro-QOL, a validated, patient-reported outcome measurement system. Methods: Consecutive patients with TIA or MIS who had (1) modified Rankin Scale (mRS) score of 0 or 1 at baseline, (2) initial NIH Stroke Scale score of ⩽5, (3) no acute reperfusion treatment, and (4) 3-month follow-up, were recruited. Recurrent stroke, disability by mRS and Barthel Index, and Neuro-QOL scores in 5 prespecified domains were prospectively recorded. We assessed the proportion of patients with impaired HRQOL, defined as T scores more than 0.5 SD worse than the general population average, and identified predictors of impaired HRQOL using logistic regression. Results: Among 332 patients who met study criteria (mean age 65.7 years, 52.4% male), 47 (14.2%) had recurrent stroke within 90 days and 41 (12.3%) were disabled (mRS >1 or Barthel Index <95) at 3 months. Any HRQOL impairment was noted in 119 patients (35.8%). In multivariate analysis, age (adjusted odds ratio [OR] 1.02, 95% confidence interval [CI] 1.01–1.04), initial NIH Stroke Scale score (adjusted OR 1.39, 95% CI 1.17–1.64), recurrent stroke (adjusted OR 2.10, 95% CI 1.06–4.13), and proxy reporting (adjusted OR 3.94, 95% CI 1.54–10.10) were independent predictors of impaired HRQOL at 3 months. Conclusions: Impairment in HRQOL is common at 3 months after MIS and TIA. Predictors of impaired HRQOL include age, index stroke severity, and recurrent stroke. Future studies should include HRQOL measures in outcome assessment, as these may be more sensitive to mild deficits than traditional disability scales.